MELATIH KETERAMPILAN REGULASI EMOSI PADA REMAJA DI PUSAT PEMBELAJARAN KELUARGA (PUSPAGA) SLEMAN - Khofifah, Reni; Aliza, Novia Fetri (Al-Amien Prenduan University, Sumenep, 2024)
Human are social creatures created with emotions and feelings. It is difficult for human not to use emotions in everyday life. Therefore, regulating emotions is necessary and the role of counselors in training emotional regulation in adolescents is also needed at the Family Learning Center (PUSPAGA) Sleman. The purpose of this study is to describe adolescent emotions, to identify how counselors train adolescent emotional regulation, to find out emotional changes in adolescents after counseling, and to find out the role of counselors in training adolescent emotional regulation at the Family Learning Center Sleman. This research applied qualitative research approach with data collection techniques using observation, interviews, and documentation. The subjects of this study were four people consisting of two counselors of PUSPAGA, a teenager, and the Head of PUSPAGA. This study results indicate that: first, the emotional description of adolescents at the Family Learning Center (PUSPAGA) initially shows negative emotions such as sadness, anxiety, fear, and so on. Second, the counselors play a role in training emotional regulation skills in adolescents by applying breathing relaxation and imagery relaxation methods. Third, the changes in adolescent emotions at the Family Learning Center (PUSPAGA) after counseling are identified. It is shown that the adolescents are able to manage their emotions to be more positive, such as being happier, more cheerful, less anxious, and less afraid. Fourth, the roles of counselors at the Family Learning Center (PUSPAGA) in training adolescent emotional regulation shown are conducting assessments, conducting counseling processes, and monitoring.